SOFT POWER: THE CONCEPT AND APPROACHES - M. M. Lebedeva (Vestnik MGIMO-Universiteta)
The article examines the correlation of two concepts: «soft power» and «propaganda» in International Relations. The author argues that within realism these concepts are used synonymously, but within neoliberalism they have fundamental differences. The parameters of comparison of the neoliberal and realistic approaches are given with reference to the concept of soft power. It is noted that, despite the differences between these approaches and between the concepts of hard power and soft power, the opposition of the concepts is not an absolute one. Soft power and hard power, according to J. Nye, can be represented as a continuum. Similarly, propaganda and soft power can also merge into one another. It is shown that, contrary to the widespread notion that the field of application determines the choice between soft and hard power (for example, education, culture are associated with soft power), in fact it does not. The coercive imposition of cultural norms, educational models is a manifestation of hard power. One of the most common tools for implementation of soft power is public diplomacy, which can be carried out through both official channels (public speeches of officials) and informal channels (NGOs, universities, etc.). It is emphasized that non-state actors can be agents of states’ soft power. There are also a number of other features of soft power that must be considered. Among them are such characteristics as specificity of a region and a country; competition in soft power of different countries in the same region; negative consequences of the use of soft power and others.